There’s an App for That? Ethical consumption in the fight against trafficking for labour exploitation - Limoncelli, Stephanie (Anti-Trafficking Review, 2020)
Among the market-based strategies being used to fight trafficking for labour exploitation are apps aimed at encouraging ethical consumption. Such apps have surfaced in tandem with the increased involvement of businesses in anti-trafficking efforts and the promotion of social entrepreneurism. In this article, I describe and critically analyse three apps aimed at individual consumers, arguing that they do little to actually address labour exploitation. They rest on questionable assumptions about consumption, employ problematic assessment methodologies, and rely on business models that do more to provide opportunities for social entrepreneurs in the burgeoning anti-trafficking field than solutions for labour exploitation in the global economy.